Adoption and correlates of the Dundee Ready Educational Environment Measure (DREEM) in the evaluation of undergraduate learning environments – a systematic review. (2nd December 2018) - Chan, Christopher Yi Wen; Sum, Min Yi; Tan, Giles Ming Yee; Tor, Phern-Chern; Sim, Kang
Abstract: Background: The Dundee Ready Educational Environment Measure (DREEM) was specifically designed to measure the undergraduate medical educational environment. This study seeks to review the adoption of DREEM internationally, and its association with different learning contexts and learner factors in order to better support our learners and facilitate future applications and research. Method: A systematic literature review was conducted on all articles that adopted and reported data using the DREEM from 1997 to April 2017. Results: Overall, the majority of 106 included studies from over 30 countries were conducted in Asia and Europe (76.4% of studies) within medical, dental, and nursing programs (86.8% of studies). Seventy-nine out of 98 studies (80.6%) which reported DREEM scores observed a mean total DREEM score within the range of "more positive than negative" (101–150 out of maximum 200 points). Higher DREEM scores were associated with better past academic achievement, quality of life, resilience, positive attitudes towards course, mindfulness, preparedness for practice, less psychological distress, and greater peer support. Conclusions: Future studies may want to examine other correlates of DREEM such as coping styles, personality profiles, burnout level, and DREEM scores can be incorporated into reviews of learning environments to ascertain longitudinal changes following educational interventions.